C−C Coupling through Nitrogen Deletion: Application to Library Synthesis. Issue 4 (21st December 2022) - Holovach, Serhii; Melnykov, Kostiantyn P.; Poroshyn, Illia; Iminov, Rustam T.; Dudenko, Dmytro; Kondratov, Ivan; Levin, Mark; Grygorenko, Oleksandr O.
Abstract: A protocol for parallel C(sp 3 )−C(sp 3 ) coupling of (hetero)aromatic aldehydes and (hetero)arylmethyl amines based on a reductive amination – "nitrogen deletion" reaction sequence has been developed. After preliminary validation experiments, an illustrative compound library of 25 members was prepared with 76 % synthetic efficiency. The estimated chemical space accessible by the proposed approach covers almost 600 000 representatives that are scarcely represented in current compound databases. Abstract : A reductive amination‐"nitrogen deletion" reaction sequence employing (hetero)aromatic aldehydes and (het)arylmethyl amines as the building blocks, and anomeric amide as the reagent was implemented for the parallel synthesis of compound libraries. The method gave access to a chemical space of over half a million compounds relevant to early drug‐discovery initiatives.